Roebuck Street, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This image shows an aerial view of Roebuck Street in Bridgetown, Barbados. The street is very busy with many persons going about their daily lives. On both sides of the street are buildings housing shops and stores. The buildings show some architectural elements of the period.Horse drawn carts line both sides of the street as vendors are plying their trade. One store sign is marked “W. L. Johnson & Co. Ltd.” This is a divided back postcard. Back of the Postcard Postcard dated: 7/11/10 The postcard reads: Dear Fred, All ok so far. We have two days in Paris and will write you from there more fully. Dad. The postcard is addressed to: Fred C. Kandace?, 161 Devonshire Street, Boston, Massachusetts. U.S.A. AL I £3 (Handwritten in Pencil). [Printed in] Germany? 1051249
Landscape; Black & white; 3 ½” x 5½ ”
Keywords: Streets; Buildings; Architecture; Windows; Roofs; Utility Poles; Street Vendors; Carts and Wagons; Commercial streets; Business districts; Business enterprises; Architectural elements; Cityscapes; City and town life; Horse-drawn carriages; Horse-drawn carts; Donkey carts